Effect of Symptomatic Treatment Given to Patients Diagnosed with Upper Respiratory Tract Infection in Emergency Department to Prescription Drug Use - Abdullah Osman Koçak (Eurasian Journal of Emergency Medicine, 2020)

(untitled)
Aim:This study aimed to investigate the effect of symptomatic treatment administered in the emergency department on the purchasing behavior for prescribed medicines among patients diagnosed with an emergency upper respiratory tract infection (URTI).Materials and Methods:This retrospective study was conducted among patients admitted to the emergency department clinic of Atatürk University in March 2016 who were discharged with a diagnosis of URTI. In total, 1,104 patients were included in the study. Using the pharmacy medulla system of the Turkish Social Security Institution, cases of patients taking prescriptions written to them were recorded. Data entry and statistical analysis were performed using SPSS statistical data program.Results:A total of 1,104 patients were examined; of them, 553 received an intervention (50.09%), 543 (49.18%) received no intervention, and eight patients (0.72%) were identified as having missing data. It was determined that 336 (60.75%) of the patients receiving an intervention received a prescription written for them, whereas 207 (37.43%) did not.Conclusion:Patients who are discharged from the emergency service with a diagnosis of URI do not receive prescriptions that will help with their actual treatment if they received any interventional therapy on arrival.